Three to get deadly - Evanovich, Janet (Evanovich, Janet. Stephanie Plum novel, 1997)
Stephanie Plum, the brassy babe in the powder blue Buick is back and she's having a bad hair day -- for the whole month of January. She's been given the unpopular task of finding Mo Bedemier, Trenton's most beloved citizen, arrested for carrying concealed, gone no-show for his court appearance. And to make matters worse, she's got Lula, a former hooker turned file clerk -- now a wannabe bounty hunter -- at her side, sticking like glue. Lula's big and blonde and black and itching to get the chance to lock up a crook in the trunk of her car. Morelli, the New Jersey vice cop with the slow-burning smile that undermines a girl's strongest resolve is being polite. So what does this mean? Has he found a new love? Or is he manipulating Steph, using her in his police investigation, counting on her unmanageable curiosity and competitive Jersey attitude? Once again, the entire One for the Money crew is in action, including Ranger and Grandma Mazur, searching for Mo, tripping down a trail littered with dead drug dealers, leading Stephanie to suspect Mo has traded his ice-cream scoop for a vigilante gun.